PENDAFTARAN HAK ATAS TANAH DENGAN SISTEM NEGATIF DAN AKIBAT HUKUMNYA DI SAMARINDA - Gokmaasi Gokmaasi (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACTGokmaasi, 2015. Registration of Rights to Land With Negative System and Legal Due in Samarinda. Guided by Abdul Munif, SH, M. Hum and Esti Royani, SH, M.PdThe registration of land in accordance with Article 19 paragraph (1) BAL, implementation of land registration is done by the government in this case the National Land Agency (BPN) in the entire territory of the Republic of Indonesia. Registration is done / conducted in a manner that is simple, easy to administer and understood by the parties concerned. Registration under paragraph (2) of Article 19, include: Measurement of soil mapping and accounting, registration of land rights and the transition, granting letters of proof applicable rights as a means of proving strong. With the registration of the land, the land which is registered land ownership certificates were issued to the beneficiary on the ground, which in practice is done in accordance with government regulations.This study aimed to determine the process of land registration in Samarinda whether it has been conducted in accordance with Government Regulation No. 24 of 1997 on Land Registration. Runs from the implementation of land registration in order to ensure legal certainty in the field of land, providing information to the interested parties, and administration.Results of the observation that the dispute is often the case in pratek surfacing is both individuals submitted through the transitional institutions and mass character through demonstrations at the National Land Agency is a land dispute. It is a result of the system of registration of land rights with a negative system as mentioned in Article 19 paragraph (2) "Letter of rights issued proof serves as strong evidence". Certificate as proof of a powerful tool means that the certificate will give legal certainty if there is no other party that feels it has on the certificate. Ari Sukanto Hutagalung classifying means which disputes can be resolved through three (3) ways: Completion directly by the parties with deliberation facilitated by the Agency Petanahan National Settlement through the Courts, which is filed by the general court in civil or criminal and Through Arbitration Institute and Alternative Dispute Resolution (Alternative Dispute Resolution). With the enactment of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, there is legal certainty to accommodate settlement of civil disputes outside the courts of general jurisdiction. Keywords: Registration of Land Rights, Negative System, Samarinda